Potencial evocado auditivo de estado estável por via aérea e via óssea em adultos ouvintes - Lira, Tatiana Vieira (2019)
Introduction: Steady State Auditory Evoked Potential (ASSR) is a promising procedure. In the children and adults populations the Auditory Steady State Responses is very important because it allows the estimation of auditory thresholds, in general 10 dB above the auditory threshold, when it is not possible to perform pure tone audiometry due to several limiting factors. Objective: To describe the difference found in the results of Pure Tone Audiometry and Auditory Steady State Response by Air and Bone Conduction, in Normal Hearing Adults. Method: Ten adults, aged between 18 and 40 years, were evaluates with Pure Tone Audiometry and ASSR, with the narrow-band CE-Chirp® stimulus at 500, 1000, 2000 and 4000 Hz. The subjects were invited to participate of the research, and presented normal hearing in pure tone audiometry, within the normal standards for the age group, in which the average of the thresholds between 500, 1000 and 2000 Hz was ≤25 dBNA (Lloyd and Kaplan,1978). Results: ten adults were included in the study, in the results of the mean differences were 14, 10, 5 and 6 dB in the right ear and 10, 9, 2, 2 in the left ear by air conduction in the frequencies 500, 1000, 2000 and 4000 Hz, respectively. The mean differences were -6, 4, -2 in the right ear and -2, 2, -2 in the left ear by bone conduction in the frequencies 1000, 2000 e 4000 Hz respectively. Conclusion: The differences found in each frequency suggest that a correction factor must be used in order to use ASSR as a tool in the Audiologic Clinic. The differences were bigger at 500 and 1000 Hz, and smaller at 2000 and 4000 Hz